2017
DOI: 10.1038/srep41462
|View full text |Cite
|
Sign up to set email alerts
|

Unloading Characteristics of Sand-drift in Wind-shallow Areas along Railway and the Effect of Sand Removal by Force of Wind

Abstract: Wind-shield walls decrease the velocity of wind-drift sand flow in transit. This results in sand accumulating in the wind-shadow zone of both windshield wall and track line, causing severe sand sediment hazard. This study reveals the characteristics of sand accumulation and the laws of wind-blown sand removal in the wind-shadow areas of three different types of windshield walls, utilizing three-dimensional numerical simulations and wind tunnel experiments and on-site sand sediment tests. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Consequently, the density of such a suspension is greater than the density of the usual flow generated in the wind tunnel when determining the aerodynamic characteristics of the body. Thus, the presence of sandy suspension in the air can impair the vessel's manoeuvrability [17] and lead to a loss of control even at a safe wind speed of 9 m/s, as identified in one of the SCA's main arguments [12], [21].…”
Section: Legal Assessment Of the Arguments Stated By The Partiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the density of such a suspension is greater than the density of the usual flow generated in the wind tunnel when determining the aerodynamic characteristics of the body. Thus, the presence of sandy suspension in the air can impair the vessel's manoeuvrability [17] and lead to a loss of control even at a safe wind speed of 9 m/s, as identified in one of the SCA's main arguments [12], [21].…”
Section: Legal Assessment Of the Arguments Stated By The Partiesmentioning
confidence: 99%
“…However, to rely on this exemption, the carrier must prove in any case that the marine hazard that caused loss/damage was unpredictable, so knowledge of the weather is a crucial factor in determining whether the carrier can rely on the exemption or is negligent, For weather conditions. Usually, the latter had to deny him entry to the canal [7], [21].…”
Section: Possible Liability For Delays and Damages Of The Goodsmentioning
confidence: 99%
“…The CTRW model [14,36,37] was applied, for example, to infiltration of anomalously diffusing particles from one material to another through a biased interface [38], and recently in the long-term prediction of 137 Cs concentration in the lakes after the Fukushima Daiichi Nuclear Power Plant accident [39], where the contamination particle ( 137 Cs) follows a long-tailed waiting time between jumps. Additionally to the ground and underground water pollution, such CTRW models could apply to model propagation of sandstorm particles, including pathogens or microbes carried by the sandstorm [40][41][42]. The sandstorm particles fly over a long distance before they arrive at the particular area and stay around for some time while the next flight takes place.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of sand sedimentation on the leeward sides of wind-break walls has recently been given serious attention. Cheng analyzed the characteristics of sand accumulation of three different types of wind-break walls by three-dimensional numerical simulations and wind-tunnel experiments and found that the wind-break wall with bottom-openings achieved improved sand dredging at high wind speeds [16]. Huang explored the characteristics of wind-blown sand flow around the wind-break wall and the causes of sand accumulation by setting up a turbulent flow-sand particle-terrain coupling model using the Lagrangian particle-tracing model and found that sand particles will be blown up and rolled back to the subgrade under the effect of vertical wind velocity and reflux [15].…”
Section: Introductionmentioning
confidence: 99%